A reserva da vida privada e a proteção de dados pessoais no contexto laboral - Pires, Rita Manuel de Brito (2020)
This internship report is the result of the choice made during the second year (third semester) of the Master's Degree in Forensic Law and Arbitration, and it seeks to reflect the theoretical-practical knowledge acquired during and following the internship at the Comissão Nacional de Protecção de Dados. The work focuses on the protection of individuals regarding privacy and the processing of personal data, in particular concerning their impact in the workplace. After contextualizing and justifying the subject to be addressed throughout the report – the first part -, we will start by presenting the Comissão Nacional de Protecção de Dados (CNPD), the host entity, developing the aspects related to the contextualization of the internship. In the third part, we will make a brief reference to the right to data protection, its historical framework and its evolution up to the present. In addition, we aim to develop the subject of the rights to privacy and data protection in the workplace. Regarding this aspect, we will emphasize the use of new technologies in a work context, aiming, in particular, to understand how the fundamental rights and interests of the employer and the worker are compatible. Still, in this chapter, we intend to highlight the geolocalization system, as well as, to discover what should be its legal framework in the portuguese legal system, in the labor context. Finally, we will make a brief prospect about the future of data protection in general, and especially in the labor realm.